Simple Closure of Duodenal Ulcer Perforation Short Term Complications and Mortality (Medical Forum Monthly, 2021)
Objective: The aim of this study was to observe short term complications and frequency of mortality after simple closure.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Department of Surgery Sandeman provincial Hospital Quetta from April 2018 to April 2019.Materials and Methods: A 40 cases for an appropriate statistical analysis. Patient selection was done by keeping the inclusion and exclusion criteria. After initial resuscitation patients were operated and perforation closed by simple closure and thorough peritoneal toilet done. Post-operatively all the patients were given I/V antibiotic, analgesic plus H. pylori eradication therapy for seven days.Results: The highest age incidence was in 30 – 40 years range with male to female ratio of 7:1. The post-operative complication seen after simple closure observed.Twenty-six (67.5%) patients developed complications which have pneumonia, wound infection, urinary tract infection, thrombophlebitis and leakage. These patients recovered with further treatment. Simple closure is best, when the etiological factors like NSAIDs, cigarette smoking is avoided. At the same instance H. Pylori eradication therapy should be administered to the H. Pylori infection positive patients to prevent recurrence of ulcer in a long term follow up.Conclusion: Pperforated duodenal ulcer had highest age incidence of 3rd decade with male female ratio of 7:1. Pperforations were repaired by simple closure. The closure of perforation by omental patch is thought to be the procedure of choice but simple closure of ulcer perforation with thorough peritoneal toilet especially in anterior wall duodenal ulcer perforation has successful results.